2014
DOI: 10.1136/annrheumdis-2014-205894
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis in knee osteoarthritis: a precursor of disease?

Abstract: Objectives It is unknown whether joint inflammation precedes other articular tissue damage in osteoarthritis. Therefore, this study aims to determine if synovitis precedes the development of radiographic knee OA (ROA). Methods The participants in this nested case-control study were selected from knees in the Osteoarthritis Initiative (OAI) that had a Kellgren Lawrence grading (KLG)=0 baseline (BL). These knees were evaluated annually with radiography and non contrast-enhanced magnetic resonance imaging (MRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
200
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(213 citation statements)
references
References 33 publications
5
200
1
7
Order By: Relevance
“…The presence of synovitis was noted, manifest by joint effusion, diffuse hyperintense signal in the fat pad on T2/ proton density/intermediate-weighted fat-suppressed sequences, thickening of the synovial membranes, and intraarticular synovial bands or debris [24,25]. Muscle atrophy and edema were also documented.…”
Section: Image Analysismentioning
confidence: 99%
“…The presence of synovitis was noted, manifest by joint effusion, diffuse hyperintense signal in the fat pad on T2/ proton density/intermediate-weighted fat-suppressed sequences, thickening of the synovial membranes, and intraarticular synovial bands or debris [24,25]. Muscle atrophy and edema were also documented.…”
Section: Image Analysismentioning
confidence: 99%
“…A nested caseecontrol study of participants selected from the OAI found that effusion-synovitis and Hoffa-synovitis, assessed from non-contrast-enhanced MRI, strongly predicted incident radiographic knee OA 37 . A prospective cohort study found that effusion-synovitis, assessed from non-contrast-enhanced T2-weighted MRI, predicted increased cartilage defects, cartilage volume loss, and increase in BMLs 38 .…”
Section: Synovitis Predicts Structural Damage and Knee Oamentioning
confidence: 99%
“…Накопленные к настоящему времени данные позволя-ют утверждать, что универсальным механизмом развития острой и хронической боли является воспаление [3][4][5], что подтверждается данными ультразвукового исследова-ния (УЗИ) и магнитно-резонансной томографии (МРТ) [6].…”
Section: ревматологияunclassified